Identifikasi Telur Cacing Soil Transmitted Helminth (STH) pada Kuku Petani Wanita di Desa Sukamandi Hilir Kecamatan Pagar Merbau Kabupaten Deli Serdang - Widiastuti Widiastuti; Lestari Rahmah (Lembaga Pengembangan Kinerja Dosen, 2024)
The most common Soil Transmitted Helmints (STH) in Indonesia are roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura), and hookworms (Ancylostoma duodenale and Necator americanus). Worms are a common disease that people in developing countries suffer from, but this cannot be underestimated because it can have a negative impact on the sufferer's health. One of the worm eggs that can cause worms is STH. Unfortunately, this has not been studied further, thus encouraging researchers to conduct a study regarding the Identification of STH Worm Eggs in the Nails of Female Farmers in Sukamandi Hilir Village, Pagar Merbau District, Deli Serdang Regency. This study aims to see the results of identifying STH worm eggs in the nails of female farmers in Sukamandi Hilir Village, Pagar Merbau District, Deli Serdang Regency. The research population was 34 nail samples from female farmers in Sukamandi Hilir Village. This type of research was descriptive. This research was carried out in the Parasitology Laboratory, Medical Laboratory Technology Department, Health Polytechnic, Ministry of Health, Medan using the Flotation method (NaCl 40%). The results of this research were obtained from 34 fingernail samples of female farmers, STH worm eggs were found in 2 samples (6%). The conclusion of this research is that female farmers in Sukamandi Hilir Village, Pagar Merbau District, Deli Serdang Regency, that some farmers lack good personal hygiene, incomplete use of PPE, and lack of personal hygiene